2015
DOI: 10.5935/1676-4285.20154585
|View full text |Cite
|
Sign up to set email alerts
|

Educational strategies with adolescents at risk from diabetes type 2: comparative study

Abstract: Aim:To compare the knowledge and behavior of adolescents with risk factors associated with type 2 diabetes mellitus after the implementation of two educational strategies. Method: Comparative and intervention study with the participation of 60 students from two public schools divided into two groups: GA (n = 30) and GB (n = 30). GA received individual educational intervention, while GB had group educational intervention.We used questionnaires to assess the level of knowledge prior to intervention, in the day a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
1
0
6
Order By: Relevance
“…That was the only study found on this population based on the data used in this review. However, an intervention study with adolescents at risk for T2DM detected those same factors, which promoted a discussion about the importance of educational actions in health instead of promoting knowledge for the target audience, contributing, thus, to changes in lifestyle of that risk group [17]. Thus, this review suggests there are still few publications on T2DM in adolescents and children, but the progression of the disease becomes a major concern worldwide.…”
Section: Discussionmentioning
confidence: 95%
“…That was the only study found on this population based on the data used in this review. However, an intervention study with adolescents at risk for T2DM detected those same factors, which promoted a discussion about the importance of educational actions in health instead of promoting knowledge for the target audience, contributing, thus, to changes in lifestyle of that risk group [17]. Thus, this review suggests there are still few publications on T2DM in adolescents and children, but the progression of the disease becomes a major concern worldwide.…”
Section: Discussionmentioning
confidence: 95%
“…Destes, treze foram desenvolvidos na região sudeste, sete no nordeste, três no sul e dois no centro-oeste. Quanto aos indicadores de qualidade utilizados para a pesquisa, dos 26 artigos, dez estavam relacionados ao DM [13][14][15][16][17][18][19][20][21][22] , nove à HA [23][24][25][26][27][28][29][30][31] , dois envolviam tanto DM quanto HA [32][33] , dois estavam direcionados ao tabagismo 34,35 , e dois ao alcoolismo 36,37 . A busca não gerou resultados relacionados à imunização/vacinação.…”
Section: Segunda Etapaunclassified
“…As intervenções ou estratégias apresentadas nos artigos selecionados foram, em sua maioria, direcionados para promoção da saúde e prevenção de agravos. Dos 25 artigos, nove estavam relacionados a programas ou grupos de educação em saúde [13][14][15]18,19,28,30,31,35 , seis utilizaram recursos tecnológicos como ferramentas para promover saúde, tais como monitoramento telefônico 16,20 , ambiente virtual 33 , telessaúde 26,37 e jogo eletrônico 21 , e dois descreviam estratégias de capacitação de profissionais para aconselhamento 22,34 . Três abordavam a orientação ou aconselhamento nutricional 23,25,29 , e três referiram a assistência farmacêutica para controle de efeitos e riscos relacionados à medicação 17,27,32 .…”
Section: Segunda Etapaunclassified
See 1 more Smart Citation
“…Sabe-se que o comportamento dos pais e familiares na oferta e consumo de refeições especiais como as guloseimas interfere diretamente no excesso de peso na infância (4) . Para que haja mudança no comportamento dos pais ou cuidadores quanto à prática alimentar não saudável, faz-se necessário incentivá-los para as atividades educativas individuais ou em grupo como apoio na construção do conhecimento visando à obtenção de resultados que promovam a alimentação saudável e, consequentemente, melhores resultados no controle da obesidade (5)(6) . Nesse sentido, no ano de 2012, criou-se o Plano Intersetorial de Prevenção e Controle da Obesidade com objetivo de prevenir e controlar a obesidade a partir da intersetorialidade, com ações de promoção à alimentação adequada e saudável e à atividade física (7) .…”
Section: Introductionunclassified